Stimulation of Cardiomyocyte Proliferation Is Dependent on Species and Level of Maturation - Yücel, Dogacan; Garay, Bayardo I.; Perlingeiro, Rita C. R.; van Berlo, Jop H. (Frontiers in Cell and Developmental Biology, 2022)
The heart is one of the least regenerative organs. This is in large part due to the inability of adult mammalian cardiomyocytes to proliferate and divide. In recent years, a number of small molecules and molecular targets have been identified to stimulate cardiomyocyte proliferation, including p38 inhibition, fibroblast growth factor 1 and Neuregulin 1. Despite these exciting initial findings, a therapeutic approach to enhance cardiomyocyte proliferation in vivo is still lacking. We hypothesized that a more comprehensive in vitro validation using live-cell imaging and assessment of the proliferative effects on various cardiomyocyte sources might identify the most potent proliferative stimuli. Here, we used previously published stimuli to determine their proliferative effect on cardiomyocytes from different species and isolated from different developmental timepoints. Although all stimuli enhanced DNA synthesis and Histone H3 phosphorylation in neonatal rat ventriculat cardiomyocytes to similar degrees, these effects varied substantially in adult mouse and human iPSC-derived cardiomyocytes. Furthermore, only p21 inhibition resulted in completion of mitosis in neonatal rat ventricular cardiomyocytes. Our results highlight p21 inhibition as a potent proliferative strategy to induce cardiomyocyte cell cycle activity across mouse, rat and human cardiomyocytes.